Jeitos de tirar samba: Wilson Batista e a poética urbana - Acuio, Joana Lopes (2012)
The research was developed from the analysis of compositions of the sambista Wilson Batista (1913-1968), aiming to observe the dynamic face of his production, which circulates and communicates with many others images, voices, experiences and stories of the imaginary of the modern city in that historical period. We seek trough the compositions of Wilson Batista to reflect about ways of composing, narrating, singing, about the communication strategies of artisan poetic and the construction of urban sonority, memories, symbolic spaces, experiences and intersections in the city. The narratives of Wilson Batista reveal the existence of many cities and ways of living that make us look for relations between samba, daily life and popular culture. Through his compositions, samba inserts itself in the city in a game full of ambiguity, putting in evidence reflections about intimate spheres of daily life, love relationships and popular experiences of the city. The research also discuss the construction of the world of samba as place of discourse, establishing conflicts, reconciliations and social intermediation, as well as mechanisms of the recording industry and radio to make themselves as integrated forms to recognize members of the modern city. The thesis is divided in three chapters: 1) Poetic Communications in the City, 2) The Lyric of Love Relationships, 3) Memories of Samba and Carioca Carnival